Expression of Thomsen-Friedenreich Antigen in colorectal cancer and association with microsatellite instability - Beatriz Farias Leão (2021)
Microsatellite instability (MSI) is a molecular phenotype due to a deficient DNA mismatch repair (dMMR). In colorectal cancer (CRC), dMMR/MSI is associated with several clinical and histopathological features, influences prognosis and is a predictive factor of response to therapy. In the daily practice, dMMR/MSI profile is identified by immunohistochemistry and/or multiplex PCR. The Thomsen-Friedenreich (TF) antigen was previously found to be a potential single marker to identify MSI-high gastric cancers. Therefore, in this study we aimed at disclosing a possible association between TF expression and MSI status in CRC. Further, we evaluated the relationship between TF expression and other clinicopathological features, including patients' survival. We evaluated the expression of the TF antigen in a cohort of 25 MSI-high and 71 microsatellite stable (MSS) CRCs. No association was observed between the expression of the TF antigen and MSI-high status in CRC. The survival analysis revealed that patients with MSI-high CRC showed improved survival when the TF antigen was expressed. This finding holds promise as it indicates the potential use of the TF antigen as a biomarker of better prognosis in MSI-high CRCs that should be validated in an independent and larger CRC cohort.